A novel energy detection scheme based on channel state estimation for cooperative spectrum sensing. (January 2017) - Budaraju, Sriramachandra Murthy; Bhagyaveni, M.A.
Abstract: A novel energy detection scheme for improved dynamic spectrum access is proposed in this paper for cognitive radio applications. To maximize the access for secondary user (SU), the availability of inactive primary user (PU) is determined based on spectrum sensing and channel state estimation. A novel energy detection scheme has been introduced to collect the spectrum sensing data of the secondary users during collection period and the length of the collection period is determined adaptively based on the number sensing data using random access. Thus, complex slot management is not necessary and computational complexity is reduced. Sensing data collection using adaptive determination is formulated as a AND rule based decision problem. Simulation results exhibit that the proposed scheme significantly outperforms the existing adaptive double threshold (ADT) technique in terms of probability of false alarm and probability of detection for various signal to noise ratio (SNR) values.